The relationship between pre-pregnancy BMI and energy and macronutrients intakes during pregnancy in women from Yucatan, Mexico - Hugo Azcorra; Federico Dickinson; José Luis Batún (Journal of Obstetrics and Gynaecology)
In this observational study, our aim was to analyse the association between pre-pregnancy BMI and adequacy rates of energy and macronutrient intakes in a sample of pregnant women from Yucatan, Mexico. From September to December 2019, we collected data on socioeconomic, pregnancy, and dietary characteristics, and took anthropometric measurements of women during household visits. Pre-pregnancy BMI was calculated from measured height and self-reported body weight. Energy and macronutrient intakes (obtained from three 24-h dietary recalls) were compared with the estimated trimester-specific requirements to calculate adequacies (%). Multiple linear regression models showed that after accounting for maternal socioeconomic characteristics and perinatal variables, each unit increase in pre-pregnancy BMI was associated with decreases of 2%, 2%, and 2.6% in energy, carbohydrate, and total fat intakes, respectively. These results were significant when under- and over-reporters were excluded from the analyses. Women who enter pregnancy with higher BMI values may voluntarily or involuntarily reduce their food intake. IMPACT STATEMENTWhat is already know about this subject? Some studies have analysed the relationship between pre-pregnancy BMI categories (normal weight, overweight, and obesity) and diet quality during pregnancy, but few studies have focussed on quantitative energy and macronutrient intakes or their adequacies in relation to pre-pregnancy BMI.What do the results of this study contribute? In this sample of Mexican women belonging to a middle socioeconomic status, we found that after excluding under- and over-reporters from the analyses and accounting for maternal socioeconomic characteristics and perinatal variables, BMI was negatively associated with adequacy intake rates of energy, carbohydrates, and total fats during pregnancy.What are the implications of these findings for clinical practice and/or further research? Women who enter pregnancy with higher BMI values may voluntarily or involuntarily reduce their food intake. These results can be used to accordingly plan diet counselling during pregnancy.